OK‐432‐stimulated chemokine secretion from human monocytes depends on MEK1/2, and involves p38 MAPK and NF‐κB phosphorylation, in vitro. Issue 4 (31st August 2012) - Olsnes, Carla; Bredholt, Therese; Olofsson, Jan; Aarstad, Hans J.
Abstract : Interaction between the immune system and cancer cells allows for the use of biological response modifiers, like OK‐432, in cancer therapy. We have studied the involvement of monocytes (MOs) in the immune response to OK‐432 by examining MCP‐1, MIP‐1α and MIP‐1β secretion, in vitro . OK‐432‐induced IL‐6/TNF‐α secretion has previously been shown to depend on mitogen‐activated protein kinases (MAPKs) ERK1/2 and p38, and we therefore investigated the role of these MAPKs in OK‐432‐induced chemokine secretion. Here we demonstrate that pharmacological MEK1/2 kinase inhibition generally impaired chemokine secretion from MOs, whereas p38 MAPK inhibition in particular reduced MIP‐1α production. Furthermore, simultaneous inhibition of MEK1/2 and Syk kinase was seen to have an additive impact on reduced MCP‐1, MIP‐1α and MIP‐1β secretion. Based on single cell flow cytometry analyses, OK‐432, lipoteichoic acid (LTA) and lipopolysaccharide (LPS) were seen to induce p38 MAPK and NF‐κB phosphorylation in MOs with different time kinetics. LTA and LPS have been shown to induce ERK1/2 phosphorylation, whereas the levels of phosphorylated ERK1/2 remained constant following OK‐432 treatment at the time points tested. Toll‐like receptors (TLRs) recognize pathogen‐associated molecular patterns, and we demonstrate increased TLR2 cell surface levels on the MO population, most profoundly following stimulation with LTA and OK‐432. Together these results indicate that modulation of MEK1/2 and p38 MAPK signalling could affect the response to OK‐432 treatment, having the potential to improve its therapeutic potential within cancer and lymphangioma treatment.